Extended Bounds of Beatty Sequence Associated with Primes - F. Deraman,; S. H. Sapar,; M. A. M. Johari,; K. A. Mohd Atan,; A. F. N. Rasedee (Blue Eyes Intelligence Engineering & Sciences Publication, 2024)
Indexed by Scopus